Biased Perceptions and Personality Traits Attribution: Cognitive Aspects in Future Interventions for Organizations - Riva, Silvia; Chinyio, Ezekiel; Hampton, Paul (Frontiers in Psychology, 2019)
In most European countries, the proportion of females and males pursuing a career in Technology and Engineering is quite different. The under-representation of women in these jobs may be attributable to a variety of factors, one of which may be the negative and stereotyped perception of these work sectors as unsuitable for women. The purpose of this study was to determine whether stereotyped perceptions impact the job representation of males and females in the Construction Industry, which is a particularly male-dominated work sector. Three construction organisations in the West Midlands (UK) were studied by means of ethnographic interviews and observations. Three (6.7%) of the 45 research participants (mean age 44.3) were women. There was a high differentiation of activities between the males and females. Biased perceptions and personality traits attribution played a fundamental role in such a differentiation. Despite some main limitations (low generalisability, lack of longitudinal findings), this study focused on some important practical implications for current work policies: changing the mindsets of people (starting from school age), using new flexible strategies and creating the role of internal advocates. The findings provide definitive evidence of the need to increase the promotion of social communication and public campaigns on gender equalities in male-dominated work sectors, taking into account the cognitive processes behind gender differences. The findings also give new hints on re-thinking the contribution of Psychology, particularly Cognitive Psychology, in fields with apparently wide gender gaps.